Research in Academia: Creating and Maintaining High Performance Research Teams. (3rd February 2019) - Olenick, Maria; Flowers, Monica; Maltseva, Tatayana; Diez-Sampedro, Ana
Abstract : As universities strive to raise their academic rank through the quality and quantity of scholarship in order to maintain their competitive edge and funding sources, faculty face pressure to increase number of publications and externally funded research (or project proposals). There are many challenges that make it difficult for faculty to meet a university's research demand, such as increased work load in academia, teaching large-size classes of students, and other strict university deadlines related to book ordering, scheduling classes, posting grades, etc. Faculty work group conflicts, faculty incivility, and dwindling grant/research funding add to faculty stress. In order to promote scholarship in academia, administrative support, collaborative work environments, mentoring, and appropriate appraisal systems are needed to enable faculty to be more productive and satisfied.